The Astra User Interface Library - Furuti, Carlos A. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1993)
Complex programs require matching user interfaces. Using basic windowing systems for implementing interfaces is a difficult task. Interface libraries, or toolkits, can be used to reduce programming effort while concentrating on actual application duties. The dual text/graphics toolkit STK was proposed, emphasizing portability and simplicity. An application program should meet similar interfaces in both modules, reducing the need for separate versions designed to run in graphic and text devices. The graphical module Astra was first implemented for UNIX workstations. Some features of Astra programming and interface elements are presented. Finally, integrating libraries into a single toolkit is discussed. Astra can be extended from the basic library. An interface editor and builder is also planned - for STK programs.